The impact of text segmentation on subtitle reading - Olivia Gerber-Morón; Agnieszka Szarkowska; Bencie Woll (Bern Open Publishing, 2018)
Understanding the way people watch subtitled films has become a central concern for subtitling researchers in recent years. Both subtitling scholars and professionals generally believe that in order to reduce cognitive load and enhance readability, line breaks in two-line subtitles should follow syntactic units. However, previous research has been inconclusive as to whether syntactic-based segmentation facilitates comprehension and reduces cognitive load. In this study, we assessed the impact of text segmentation on subtitle processing among different groups of viewers: hearing people with different mother tongues (English, Polish, and Spanish) and deaf, hard of hearing, and hearing people with English as a first language. We measured three indicators of cognitive load (difficulty, effort, and frustration) as well as comprehension and eye tracking variables.  Participants watched two video excerpts with syntactically and non-syntactically segmented subtitles. The aim was to determine whether syntactic-based text segmentation as well as the viewers' linguistic background influence subtitle processing. Our findings show that non-syntactically segmented subtitles induced higher cognitive load, but they did not adversely affect comprehension. The results are discussed in the context of cognitive load, audiovisual translation, and deafness.